2020
DOI: 10.1186/s12879-020-04998-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and molecular characterization of Streptococcus pneumoniae carriage strains in pre-school children in Arkhangelsk, northern European Russia, prior to the introduction of conjugate pneumococcal vaccines

Abstract: Background The 13-valent Pneumococcal Conjugate Vaccine (PCV-13) was introduced in the National Immunization Programme (NIP) schedule in Russia in March 2014. Previously, the 7-valent Pneumococcal Conjugate Vaccine (PCV-7) was marketed in Russia in 2009 but has never been offered for mass vaccination. A carriage study was performed among children in Arkhangelsk in 2006. The objective was to determine the prevalence of carriage, serotype distribution, antimicrobial susceptibility and the molecular structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…However, the prevalence of pneumococcal serotypes in our region was slightly different from those in developing countries and regions e.g. Thailand (6B, 23F, 14) ( Hocknell et al, 2019 ), Malaysia (14, 6B, 19A, 6A) ( Arushothy et al, 2019 ), Mexico (19A, 3, 15B, 19F) ( Echaniz-Aviles et al, 2019 ) and northern Russia (19F, 23F, 6A) ( Vorobieva S Jensen et al, 2020 ), and were totally different from those in developed countries e.g. the USA (35B, 3, 11A/D) ( Suaya et al, 2020 ), the UK and Ireland (3, 8, 15A) ( Pick et al, 2020 ), and Japan (12F, 3, 23A) ( Yanagihara et al, 2021 ).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, the prevalence of pneumococcal serotypes in our region was slightly different from those in developing countries and regions e.g. Thailand (6B, 23F, 14) ( Hocknell et al, 2019 ), Malaysia (14, 6B, 19A, 6A) ( Arushothy et al, 2019 ), Mexico (19A, 3, 15B, 19F) ( Echaniz-Aviles et al, 2019 ) and northern Russia (19F, 23F, 6A) ( Vorobieva S Jensen et al, 2020 ), and were totally different from those in developed countries e.g. the USA (35B, 3, 11A/D) ( Suaya et al, 2020 ), the UK and Ireland (3, 8, 15A) ( Pick et al, 2020 ), and Japan (12F, 3, 23A) ( Yanagihara et al, 2021 ).…”
Section: Discussionmentioning
confidence: 55%
“…These results suggest that S. pneumoniae may have multiple origins in China. In addition, the prevalent STs in China were different from those in other countries, such as Japan ( Nakano et al, 2016 ), northern Russia ( Vorobieva S Jensen et al, 2020 ), Iran ( Talebi et al, 2016 ) and Latin America ( Moreno et al, 2020 ), strongly suggesting the diversity of S. pneumoniae on a global scale.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study reported that serotype 15B/C emerged as the predominant non-vaccine serotype and was widely disseminated 16 . Additionally, serotype predominance in relation to age group was observed in a previous study that revealed serotype 14 as the most common serotype in children less than 48 months of age in Russia 17 . This was in agreement with our finding that serotype 14 and 6A/B was predominant among ≤ 5 year-old group.…”
Section: Discussionmentioning
confidence: 60%
“…There is currently no national surveillance system for pneumococcal disease in Russia [17,18]. However, a number of studies have reported data on pneumococcal infection incidence and distribution of circulating pneumococcal serotypes [18][19][20][21][22][23]. S. pneumoniae was responsible for 2-20 % of bacterial meningitis cases in children under 5 years of age in [2005][2006], and the incidence of pneumococcal meningitis in the same age group was 4-8 cases per 100 000 [17,19].…”
Section: Introductionmentioning
confidence: 99%